Factors Associated with Underweight among Children of Former-Kamaiyas in Nepal - Khatri, Resham B.; Mishra, Shiva R.; Khanal, Vishnu; Choulagai, Bishnu (Frontiers in Public Health, 2015)
Background Bonded labor was a tradition in Nepal since the 16th century. In 2002, the Government of Nepal freed Kamaiyas and gave the newly freed individuals support for basic living. Many children of former-Kamaiyas live below subsistence level and are vulnerable to undernutrition. The aim of this study was to identify the factors associated with underweight among the children of former-Kamaiyas. Methods We conducted the community based cross-sectional study from June-December, 2012. Face-to-face interviews were conducted using semi-structured questionnaires with randomly selected mothers of 280 children under five years of age from former-Kamaiya families residing in Banke district. We also measured the weight and height of the children. Undernutrition was defined according to the World Health Organization (WHO) child growth standards. Factors associated with underweight were examined using a chi-square test followed by multivariate logistic regression. Results Out of 280 children studied, 116 (41.4%) were underweight (<-2 Standard Deviation (SD) weight-for-age), 156 (55.7%) were stunted (<-2SD height-for-age), and 52 (18.6%) were wasted (<-2SD weight-for-height). Females were more likely to be underweight than males (adjusted Odds Ratio (aOR) =1.696, 95% Confidence Interval (CI) = 1.026-2.804). Children were less likely to be underweight if they were having daily bath (aOR==0.532; 95% CI=0.314-0.899) or if their mothers were ≥24 years of age (aOR=0.440; 95% CI=0.266-0.727). Conclusions The proportion of underweight, stunting and wasting was more than the national average among the children of former-Kamaiyas. Female children were more likely to be underweight whereas children who were being bathed daily and with mothers whose age was ≥24 years were less likely to be underweight.